Network dynamic defense system based on holographic transformation. (May 2020) - Tan, Jinglei; Lei, Cheng; Zhang, Hongqi; Hu, Hao; Zhang, Hengwei
Aimed at the problem of the boundary defense easily being out of availability caused by the static network structure, a novel dynamic enterprise network defense system based on holographic transformation is designed and implemented. To increase the uncertainty of network structure and the position of target nodes, the network view is dynamically changed by constantly transforming endpoint information. Virtual endpoint mutation and hopping period selection are achieved by the hopping address generation module. It takes the advantages of anti-collision and good randomicity of the Chinese national SM3 hash algorithm. The full-cycle hopping period is managed and controlled by the hopping period management mechanism based on the ciphertext policy attribute-based broadcast holographic transformation. Experiments show that the system achieves expected security goals and has good interactivity and high stability.